PEMBERDAYAAN GURU BIMBINGAN KONSELING MADRASAH DAERAH 3T DALAM MENGATASI MASALAH PSIKOSOSIAL REMAJA DENGAN MENGGUNAKAN ECO ART COUNSELING - Amirah Diniaty; Siti Kulsum; Riswani Riswani; Salmiah Salmiah (As-Sidanah, 2025)
School Counselors have the right to self-improvement to enhance their professional competencies. However, not all counselors have such opportunities, especially those in underdeveloped, frontier, and outermost regions (3T areas). This article discusses the self-development of counselors in a 3T area using eco-art counseling techniques to address psychosocial issues in adolescents, applying an Asset Based Community Development/ABCD approach. The service results indicate that this mentorship could improve the professional competencies of madrasah counselors in handling student psychosocial cases. Students were able to express their emotions through creative expression using local natural materials such as fine Natuna Marus beach sand, gonggong shells, and plants that are mostly found in Natuna such as cloves. They are interacting and collaborating with counselors and getting support from their friends who give positive responses to their work. Creative expressions led to artworks with potential economic values, such as motifs for hijab, Natuna's typical sarung.The community service recommends that future services should further specify student psychosocial issues and develop an educational module for eco-art counseling.